Anionic nonionic surfactant, preparation method and application thereof, and method for reducing viscosity of thickened oil

By preparing an anionic nonionic oligomeric surfactant with synergistic action of multiple amphiphilic motifs, the problem of insufficient tolerance to calcium and magnesium ions in the prior art is solved, and the effect of efficient viscosity reduction of heavy oil in high calcium and magnesium and high mineralization environments is achieved.

CN119684170AActive Publication Date: 2025-03-25CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311238610.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The prior art neutral nonionic surfactants have insufficient tolerance to calcium and magnesium ions, especially in reservoir environments with high mineralization and high calcium and magnesium ion content, resulting in the electric double layer on the surface of the surfactant aggregate being compressed and precipitated.

Method used

An anionic nonionic surfactant is used, which opens the ring by an amine compound with 1,2-epoxy compound and sulfonates with a sulfonating agent to prepare an oligomeric surfactant with a synergistic effect of multiple amphiphilic moieties to improve its tolerance to calcium and magnesium ions.

Benefits of technology

In oil reservoir environments with high calcium and magnesium and high mineralization, the new surfactant can maintain good interfacial activity, reduce oil-water interface tension, form a low viscosity oil-in-water emulsion, and achieve a high-efficiency viscosity reduction rate of thick oils above 97%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684170A_ABST
    Figure CN119684170A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thick oil emulsification and viscosity reduction, and discloses an anionic and nonionic surfactant, a preparation method and application thereof, and a thick oil viscosity reduction method, the surfactant comprises a compound having a structure represented by formula (I) # imgabs0 #, each R2 is independently selected from H and C1-C4 alkyl groups, # imgabs1 # R5 and R6 are independently substituted or unsubstituted C8-C22 alkenyl groups, C8-C22 alkyl groups or heteroalkyl groups, and M is alkali metal; each R4 is independently selected from H, a C1-C4 alkyl group or # imgabs2 # and at least one R2 or R4 is # imgabs3 # R1 and R3 is independently selected from a substituted or unsubstituted C1-C20 alkylene group; in the surfactant, the average value of the s value is 1-100. The surfactant has very strong calcium and magnesium resistance, has strong interfacial activity in formation water with high calcium and magnesium ion concentration and high salinity, and has excellent emulsification and viscosity reduction capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy oil emulsification and viscosity reduction, and in particular to an anionic nonionic surfactant, a preparation method and application thereof, and a heavy oil viscosity reduction method. Background Art

[0002] my country has large reserves of heavy oil resources and a low level of utilization. The efficient development and utilization of heavy oil resources is of strategic significance to ensuring national energy security. However, the high viscosity and poor fluidity of heavy oil make improving the recovery rate of heavy oil a global problem. In recent years, surfactant-based viscosity reducers have been proven to be able to emulsify heavy oil to form water-in-oil emulsions, achieving efficient utilization of heavy oil. Since anionic non-ionic surfactants have low adsorption loss in the formation and excellent emulsification and viscosity reduction performance, they have become one of the most widely used and widely used heavy oil viscosity reducers.

[0003] With the deepening of heavy oil resource development and the urgent strategic demand of the country for oil resources, the technology of improving the recovery rate of heavy oil reservoirs with more stringent reservoir conditions has become a hot topic. The formation water of harsh oil reservoirs generally has the characteristics of high mineralization and high calcium and magnesium ion content. Taking the western oil reservoirs in my country as an example, the mineralization of formation water in some blocks is higher than 100,000 mg / L, and the total content of calcium and magnesium ions is as high as 7,000 mg / L or more. However, the binding and shielding ability of calcium and magnesium ions with the negatively charged head groups of anionic non-ionic surfactants is strong, resulting in a significant compression of the double electric layer on the surface of the surfactant aggregates, and finally precipitation. The commonly used single-chain anionic non-ionic surfactant viscosity reducers alkyl alcohol ether carboxylates (AEC) and alkyl alcohol ether sulfates (AES) have weak tolerance to calcium and magnesium ions. Alkylphenol ether sulfates (NPS) have relatively good resistance to calcium and magnesium ions, but their extreme tolerance concentration to calcium and magnesium ions is lower than 5,000 mg / L, and they cannot be used in high calcium and magnesium formation water in western oil reservoirs.

[0004] CN111117587A discloses a high calcium and magnesium resistant anionic nonionic surfactant, specifically a fatty alcohol polyoxyethylene ether carboxylate, which can resist calcium and magnesium 2000mg / L and is suitable for high temperature and high salt reservoirs. CN102504792A discloses a dialkyl ether sodium disulfonate surfactant, which can resist calcium and magnesium up to 13000mg / L after compounding with nonylphenol polyoxyethylene ether or fatty alcohol polyoxyethylene ether and anhydrous ethanol to form a composite oil displacement system, but the compounding system has the problem of chromatographic separation during application and poor stability. CN112195021A discloses a Gemini type alkylphenol polyoxyethylene ether sulfosuccinate, which can resist calcium and magnesium 5000mg / L in a single dose, but the alkylphenol type surfactant has reproductive toxicity and its application field is limited.

[0005] It can be seen that the salt resistance and calcium and magnesium ion resistance of a single dose of anionic nonionic surfactants in the prior art are still not ideal. Although the composite system can have a higher calcium and magnesium resistance, there are chromatographic separation problems and it is impossible to take into account high stability. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem of poor salt resistance and calcium and magnesium ion resistance of surfactants in the prior art, and to provide an anionic nonionic surfactant and a preparation method and application thereof, and a method for reducing the viscosity of heavy oil. The anionic nonionic surfactant has strong salt resistance and calcium and magnesium ion resistance, excellent interfacial activity under conditions of high mineralization and high calcium and magnesium ion content, and high heavy oil viscosity reduction rate.

[0007] In order to achieve the above object, the present invention provides an anionic nonionic surfactant, which comprises a compound having a structure shown in formula (I),

[0008]

[0009] Wherein, each R2 is independently selected from H, C1-C4 alkyl, R5 and R6 are each independently substituted or unsubstituted C8-C 22 Alkenyl, C8-C 22 alkyl or heteroalkyl, M is an alkali metal; each R4 is independently selected from H, C1-C4 alkyl or and at least one R2 or R4 is R1 and R3 are each independently selected from substituted or unsubstituted C1-C 20 of alkylene;

[0010] In the surfactant, the average value of s value is 1-100.

[0011] The second aspect of the present invention provides a method for preparing an anionic nonionic surfactant, comprising the following steps:

[0012] (1) subjecting an amine compound to a first ring-opening reaction with a 1,2-epoxy compound to obtain an intermediate oligomer alcohol;

[0013] Wherein, the amine compound has a structure shown in formula (i),

[0014]

[0015] Wherein, each R2' is independently selected from H, C1-C4 alkyl or Each R4' is independently selected from H or C1-C4 alkyl; R1 and R3 are independently selected from substituted or unsubstituted C1-C 20Alkylene, C2-C 20 Heteroalkylene and C6-C 20 At least one of the arylene groups;

[0016] The structure of the 1,2-epoxide compound is represented by R5 and R6 are each independently substituted or unsubstituted C8-C 22 Alkenyl, C8-C 22 An alkyl or heteroalkyl group;

[0017] (2) in the presence of a base, subjecting the intermediate oligomeric alcohol to a second ring-opening reaction with ethylene oxide to obtain a polyether intermediate;

[0018] (3) contacting the polyether intermediate with a sulfonating agent to carry out a sulfonation reaction to obtain a mixture;

[0019] (4) using an alkaline substance containing an element M to adjust the pH value of the mixture to be greater than or equal to 7, and then performing solid-liquid separation; M is an alkali metal.

[0020] The third aspect of the present invention provides the use of the anionic nonionic surfactant described in the first aspect or the anionic nonionic surfactant prepared by the preparation method described in the second aspect in heavy oil viscosity reduction production.

[0021] A fourth aspect of the present invention provides a method for reducing the viscosity of heavy oil, comprising: mixing a viscosity reducer with the heavy oil; the viscosity reducer comprises the surfactant described in the first aspect or the anionic nonionic surfactant prepared by the preparation method described in the second aspect;

[0022] Preferably, the total mass concentration of calcium and magnesium ions in the formation water of the reservoir where the heavy oil is located is higher than 6000 mg / L, and the total mineralization is higher than 80000 mg / L.

[0023] The anionic nonionic surfactant provided by the present invention has a strong calcium and magnesium resistance, and has strong interfacial activity in high calcium and magnesium ion concentration and high mineralization formation water, which can reduce the interfacial tension to 10 -2 mN / m range, and can be applied to high calcium and magnesium, high mineralization reservoir formation water environment with calcium and magnesium ion content higher than 6000 mg / L. It has excellent emulsification and viscosity reduction ability for heavy oil, with a viscosity reduction rate higher than 97%, and can be used as a viscosity reduction development aid for heavy oil cold production in reservoirs with high calcium and magnesium ion content.

[0024] The anionic nonionic surfactant provided by the present invention uses amine and 1,2-epoxy compound as starting materials, and is prepared by two-step ring-opening reaction and one-step sulfonation reaction to obtain a product. The preparation method provided is simple to operate, has high yield, and is easy to industrially scale up. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1is the MALDI-TOF mass spectrum of the intermediate tetramer alcohol prepared in Example 1 of the present invention;

[0026] Figure 2 The polyether intermediate prepared in Example 1 of the present invention 1 H NMR spectra;

[0027] Figure 3 is the infrared spectrum of the anionic nonionic surfactant prepared in Examples 1-3 of the present invention;

[0028] Figure 4 is the MALDI-TOF mass spectrum of the intermediate hexamer alcohol prepared in Example 2 of the present invention;

[0029] Figure 5 is the polyether intermediate obtained in Example 2 of the present invention 1 H NMR spectra;

[0030] Figure 6 is the MALDI-TOF mass spectrum of the intermediate dimer alcohol prepared in Example 3 of the present invention;

[0031] Figure 7 is the polyether intermediate obtained in Example 3 of the present invention 1 H NMR spectra. DETAILED DESCRIPTION

[0032] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0033] In the present invention, the wavy line in a substituent, e.g. Indicates the bonding position of the R group.

[0034] The first aspect of the present invention provides an anionic nonionic surfactant, wherein the surfactant comprises a compound having a structure shown in formula (I),

[0035]

[0036] Wherein, each R2 is independently selected from H, C1-C4 alkyl, R5 and R6 are each independently substituted or unsubstituted C8-C 22 Alkenyl, C8-C 22alkyl or heteroalkyl, M is an alkali metal; each R4 is independently selected from H, C1-C4 alkyl or and at least one R2 or R4 is R1 and R3 are each independently selected from substituted or unsubstituted C1-C 20 of alkylene;

[0037] In the surfactant, the average value of s value is 1-100.

[0038] The anionic nonionic surfactant provided by the present invention has a strong ability to resist calcium and magnesium ions, which is the result of the synergistic effect of multiple anionic nonionic amphiphilic moieties in the molecule. The multiple amphiphilic moieties contained in the surfactant can not only resist the electrical shielding of calcium and magnesium ions through polyoxyethylene ether groups, but also form a composite structure with calcium and magnesium ions in the form of spatial coordination, thereby further improving the extreme tolerance concentration of calcium and magnesium ions, and having a strong ability to resist calcium and magnesium.

[0039] According to the present invention, each R2 in formula (I) is independently selected from H, C1-C4 alkyl, and at least one R2 or R4 is It is understood that, in the surfactant provided by the present invention, as long as at least one head group in the structure shown in formula (I) is In the present invention, "C1-C4 alkyl" refers to an alkyl group having 1 to 4 carbon atoms, which may be a straight chain or branched chain alkyl group, for example, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group or an isobutyl group.

[0040] According to some preferred embodiments of the present invention, in formula (I), at least two R2 are The remaining R2 may be H or a C1-C4 alkyl group.

[0041] According to some other preferred embodiments of the present invention, in formula (I), at least two R2 are And in each R2, at least one R4 is

[0042] According to some preferred embodiments of the present invention, M is Na or K.

[0043] In a further preferred embodiment, the surfactant comprises at least one of the compounds having the following structural formula,

[0044]

[0045]

[0046] According to some preferred embodiments of the present invention, R1 and R3 are each independently selected from substituted or unsubstituted C1-C 12 of alkylene.

[0047] In the present invention, R1 and R3 may be the same or different. 12 The alkylene group may be a straight chain or branched alkylene group, for example, a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a heptylene group, an octylene group, a nonylene group, a decylene group or any one of their isomers. One or more carbon atoms in the alkylene group may also be optionally substituted by one or more of a cycloalkyl group, an aryl group or a heteroatom, and the heteroatom may be selected from at least one of O, S and N.

[0048] Preferably, R1 and R3 are selected from any one of the structures shown in formula (1) to formula (16);

[0049]

[0050]

[0051] In some preferred embodiments of the present invention, in formula C, R1 and R3 are preferably

[0052] In the present invention, "C8-C 22 "Alkyl" refers to an alkyl group having 8 to 22 carbon atoms, such as n-octyl, n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, etc. "Heteroalkyl" refers to a group formed by replacing at least one carbon atom in the alkyl group with a heteroatom, such as O, S or N.

[0053] According to some preferred embodiments of the present invention, R5 and R6 are each independently n-octyl, n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, (2-ethylhexyloxy)methyl, octenyl or C8-C 10 Preferably, R5 is n-octyl, n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, (2-ethylhexyloxy)methyl, octenyl or C8-C 10 Alkoxymethyl, R6 is hydrogen. In the above preferred case, it is beneficial to improve the oil-water amphiphilicity of the surfactant, thereby further improving the surface activity of the product.

[0054] According to some preferred embodiments of the present invention, the average value of s in the surfactant is 2-20. The inventors of the present invention have found in their research that when the s value is too large, the space volume of the polyoxyethylene segment is large, which may be unfavorable for the close arrangement of molecules at the oil-water interface; and when the s value is too small, it may lead to poor molecular solubility. When the average value of s in the surfactant is within the above preferred range, it is beneficial to further improve the interfacial activity of the surfactant.

[0055] According to the present invention, the surfactant is an oligomeric surfactant, and preferably, the molecular weight of the surfactant does not exceed 10000 g / mol, preferably 400-8000 g / mol, and more preferably 2000-6000 g / mol.

[0056] In the present invention, the molecular weight of the surfactant is calculated based on the molecular weight of the intermediate oligomer alcohol and the average number of s. Controlling the molecular weight of the surfactant within the above preferred range is conducive to the efficient synergistic effect between multiple amphiphilic units in the product, while avoiding the problems of poor solubility and unsatisfactory interfacial activity caused by too high molecular weight.

[0057] The second aspect of the present invention provides a method for preparing an anionic nonionic surfactant, comprising the following steps:

[0058] (1) subjecting an amine compound to a first ring-opening reaction with a 1,2-epoxy compound to obtain an intermediate oligomer alcohol;

[0059] Wherein, the amine compound has a structure shown in formula (i),

[0060]

[0061] Wherein, each R2' is independently selected from H, C1-C4 alkyl or Each R4' is independently selected from H or C1-C4 alkyl; R1 and R3 are independently selected from substituted or unsubstituted C1-C 20 Alkylene, C2-C 20 Heteroalkylene and C6-C 20 At least one of the arylene groups;

[0062] The structure of the 1,2-epoxide compound is represented by R5 and R6 are each independently substituted or unsubstituted C8-C 22 Alkenyl, C8-C 22 An alkyl or heteroalkyl group;

[0063] (2) in the presence of a base, subjecting the intermediate oligomeric alcohol to a second ring-opening reaction with ethylene oxide to obtain a polyether intermediate;

[0064] (3) contacting the polyether intermediate with a sulfonating agent to carry out a sulfonation reaction;

[0065] (4) Using an alkaline substance containing an element M to adjust the pH value of the mixture I to be greater than or equal to 7; M is an alkali metal.

[0066] According to the present invention, in formula (i), the definitions of R1, R3, R5 and R6 are the same as those in formula (I), and are not repeated here.

[0067] Preferably, the amine compound is selected from at least one of the compounds having structures represented by formula (17) to formula (43);

[0068]

[0069]

[0070] According to some preferred embodiments of the present invention, the 1,2-epoxy compound is selected from 1,2-epoxydecane, 1,2-epoxytetradecane, 1,2-epoxyhexadecane, 1,2-epoxyoctadecane, 1,2-epoxyeicosane, 2-ethylhexyl glycidyl ether, 1,2-epoxy-9-decene and C8-C 10 At least one of alkyl glycidyl ethers.

[0071] According to the present invention, preferably, in step (1), the molar ratio of the 1,2-epoxy compound to the amine compound is (1-10):1, preferably (1.1-2):1, wherein the molar amount of the amine compound is based on the molar amount of the NH bond in the molecule.

[0072] Preferably, the conditions of the first ring-opening reaction include: temperature of 30-150° C., preferably 30-80° C.; time of 4-72 h, preferably 12-18 h.

[0073] According to the present invention, preferably, the first ring-opening reaction is carried out in the presence of an organic solvent. The present invention has a wide range of selection for the organic solvent. As long as it can dissolve and disperse the reactants, any organic solvent commonly used in the art can be applied to the present invention. For example, the organic solvent can be at least one of methanol, ethanol, isopropanol and dichloromethane.

[0074] According to some preferred embodiments of the present invention, in step (2), the mass ratio of ethylene oxide to the intermediate oligomeric alcohol is (20-1000):100, preferably (50-500):100.

[0075] According to the present invention, the second ring-opening reaction in step (2) is carried out in the presence of a base. The present invention has a wide range of selection for the base. Preferably, the base is selected from alkali metal hydroxides, preferably sodium hydroxide and / or potassium hydroxide.

[0076] According to some preferred embodiments of the present invention, the mass ratio of the base to the intermediate oligomeric alcohol is (0.1-2):100, preferably (0.25-1):100.

[0077] According to the preparation method of the present invention, the second ring-opening reaction is a high temperature and high pressure reaction, and the reaction is carried out in an autoclave. Preferably, the conditions of the second ring-opening reaction include: reaction temperature of 80-180°C, reaction time of 4-10h, and reaction pressure of 0.3-1MPa.

[0078] In a further preferred embodiment, the second ring-opening reaction comprises: mixing the intermediate oligomeric alcohol with a base at a first constant temperature, and then adding ethylene oxide to react at a second constant temperature, wherein the first constant temperature does not exceed 100° C., preferably 80-100° C., and the second constant temperature is 100-180° C., preferably 120-160° C. The above preferred embodiment is advantageous in improving the efficiency of the ring-opening reaction between the alcohol hydroxyl group and ethylene oxide.

[0079] Preferably, the second ring-opening reaction is carried out under stirring conditions.

[0080] The present invention has a wide selection range for the sulfonating agent, and conventional sulfonating agents in the art can be applied to the present invention. Preferably, the sulfonating agent is selected from at least one of sulfur trioxide pyridine complex, oleum, sulfur trioxide, concentrated sulfuric acid, chlorosulfonic acid, and aminosulfonic acid. Preferably, the content of active SO3 in the sulfur trioxide pyridine complex is 45-55wt%.

[0081] According to some preferred embodiments of the present invention, the ratio of the molar amount of the sulfonating agent to the molar amount of the polyether intermediate is (0.5-3):1, preferably (1-1.5):1, wherein the molar amount of the polyether intermediate is based on the molar amount of the hydroxyl groups contained.

[0082] According to the present invention, the polyether intermediate can be directly contacted with the sulfonating agent, or the polyether intermediate can be first dissolved in an organic solvent and then the sulfonating agent is added. The present invention has no special requirements for the amount and type of the organic solvent, and any organic solvent that can dissolve the polyether intermediate and does not participate in the reaction can be used in the present invention.

[0083] Preferably, the organic solvent is selected from dichloromethane and / or chloroform.

[0084] Preferably, the mass ratio of the polyether intermediate to the organic solvent is (0.1-10):1, preferably (0.5-2):1.

[0085] According to some preferred embodiments of the present invention, step (3) comprises: adding a sulfonating agent to the polyether intermediate or its organic solution, and then performing a sulfonation reaction.

[0086] The sulfonating agent may be added dropwise. Preferably, during the addition of the sulfonating agent, the temperature of the reaction zone system is controlled to be -10 to 5° C., for example, the reaction system may be placed in an ice water bath.

[0087] Furthermore, after the sulfonating agent is added, the temperature is raised to the sulfonation reaction temperature to carry out the sulfonation reaction. Preferably, the sulfonation reaction temperature is 10-40°C, preferably 15-30°C, and the reaction time is 1-8h, preferably 2-6h.

[0088] When the polyether intermediate is provided in the form of an organic solution, the method further comprises the step of removing the organic solvent from the product obtained by the sulfonation reaction. The present invention has no particular limitation on the specific method for removing the organic solvent, and any conventional method in the art can be used, such as rotary evaporation.

[0089] According to some preferred embodiments of the present invention, in step (4), an alkaline substance containing element M is used to adjust the pH value of the mixture to 7-9.

[0090] The present invention has no particular limitation on the method for introducing the alkaline substance, as long as the pH value of the mixture can be adjusted to be greater than or equal to 7. The alkaline substance can be directly introduced into the mixture, or provided in the form of an aqueous solution.

[0091] Preferably, in step (4), the alkaline substance is selected from alkali metal hydroxides, preferably at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide, and more preferably sodium hydroxide and / or potassium hydroxide.

[0092] According to the present invention, in order to improve the purity of the product, preferably, the preparation method further comprises: recrystallizing the product obtained by the sulfonation reaction.

[0093] Preferably, the recrystallization solvent is selected from at least one of methanol, ethanol, acetone and ethyl acetate, for example, it can be a mixture of ethanol and ethyl acetate, a mixture of methanol and ethyl acetate, a mixture of ethanol and acetone, or a mixture of methanol and acetone. Preferably, the recrystallization solvent is a mixture of ethanol and ethyl acetate, preferably, the volume ratio of ethanol to ethyl acetate is 1:5-30.

[0094] The third aspect of the present invention provides the use of the anionic nonionic surfactant described in the first aspect or the anionic nonionic surfactant prepared by the preparation method described in the third aspect in heavy oil viscosity reduction production.

[0095] The anionic nonionic surfactant provided by the present invention has excellent emulsification and viscosity reduction capabilities for heavy oil. In particular, the surfactant can be applied to high calcium and magnesium and high mineralization oil reservoir formation water environments with calcium and magnesium ion contents higher than 6000 mg / L. The viscosity reduction rate for heavy oil is higher than 97%, and the surfactant can be used as a viscosity reduction development aid for heavy oil cold production in oil reservoirs with high calcium and magnesium ion contents.

[0096] The fourth aspect of the present invention provides a method for reducing the viscosity of heavy oil, comprising: mixing a viscosity reducer with the heavy oil; the viscosity reducer comprises the surfactant described in the first aspect or the anionic nonionic surfactant prepared by the preparation method described in the second aspect.

[0097] Preferably, the total mass concentration of calcium and magnesium ions in the formation water of the reservoir where the heavy oil is located is higher than 6000 mg / L, and the total mineralization is higher than 80000 mg / L. More preferably, the total mass concentration of calcium and magnesium ions in the formation water of the reservoir where the heavy oil is located is 6000-40000 mg / L, and the total mineralization is 80000-150000 mg / L.

[0098] In the prior art, the technical limit of the single-dose anti-calcium and magnesium ability of anionic nonionic surfactants is 7000 mg / L of calcium and magnesium. The anionic nonionic surfactant provided by the present invention can break through the limit tolerance concentration of calcium and magnesium ions for a single dose in the prior art. In high calcium and magnesium, high mineralization formation water, anionic nonionic oligomeric surfactants can be enriched at the oil-water interface, reduce the oil-water interfacial tension and interfacial Gibbs free energy, show good interfacial activity, and promote phase transition to form a low-viscosity water-in-oil emulsion, and finally reach a viscosity reduction rate of more than 97%. Therefore, the new anionic nonionic oligomeric surfactant provided by the present invention has broad application potential in the field of cold production viscosity reduction and production increase in high calcium and magnesium, high mineralization oil fields.

[0099] Preferably, the viscosity reducing oil displacement agent further contains solvent water, and the concentration of the surfactant in the viscosity reducing agent is 100-5000 mg / L, preferably 500-3000 mg / L.

[0100] According to some preferred embodiments of the present invention, relative to 1L of the heavy oil, the amount of the viscosity reducer is 0.43-2.3L, preferably 0.5-1.5L.

[0101] The present invention will be described in detail below through examples.

[0102] Unless otherwise specified, the instruments, reagents, materials, etc. involved in the following examples are conventional instruments, reagents, materials, etc. already available in the prior art and can be obtained through regular commercial channels.

[0103] The main raw material information used in the examples is shown in Table 1:

[0104] Table 1

[0105] Product Name CAS Number source Part Number 1,2-Epoxytetradecane 3234-28-4 TCI E0314 Chlorosulfonic acid 7790-94-5 Sinopharm 800356601 Sodium Lauryl Ether Sulfate (SLES) 68585-34-2 Aladdin S304383 Ethylenediamine 107-15-3 Aladdin E112642 Tris(2-aminoethyl)amine 4097-89-6 Innochem A48717 N,N'-Dimethylethylenediamine 110-70-3 Innochem A44864 Ethylene oxide 75-21-8 Aladdin E105779

[0106] Example 1

[0107] The anionic nonionic tetrameric surfactant TES has the following preparation process:

[0108]

[0109] (1) 0.6 g (10 mmol) of ethylenediamine was added to a solution of 12.7 g (60 mmol) of 1,2-epoxytetradecane in anhydrous ethanol (50 mL), and the mixture was heated to 78.5°C and refluxed for 24 h. After the reaction was completed, the anhydrous ethanol solvent was removed by a rotary evaporator, the crude product was dissolved in dichloromethane, and then purified by eluting with dichloromethane / methanol on a silica gel column and vacuum dried to obtain 9.0 g of a white powdery intermediate tetramer (i), with a calculated yield of 99 wt%. (The yield here is: the percentage of the actual yield to the theoretical yield calculated based on the complete reaction of ethylenediamine, the same applies to the following examples)

[0110] The intermediate tetramer alcohol was characterized by MALDI-TOF mass spectrometry. Figure 1 A peak of 910.364 appeared in the spectrum, which was the molecular ion peak of the intermediate tetramer alcohol, proving that the target structure was obtained.

[0111] (2) 100 parts by weight of the intermediate tetrapolyol was added to the autoclave, and then 0.5 parts by weight of KOH catalyst was added. The autoclave was sealed, and the air in the autoclave, the feed kettle and the feed pipe was displaced with dry nitrogen. The temperature was raised and stirred, and vacuum was evacuated with a vacuum pump. When the temperature reached 100°C, the vacuum was stopped. 135 parts by weight of ethylene oxide was added to the feed kettle, pressurized to 0.4 MPa, mechanical stirring was started, and then the feed valve was opened to slowly feed the material. During the process, the reaction temperature was controlled at 140°C and the pressure was controlled at 0.4 MPa. After the addition was completed, the reaction was stopped for 6 hours and the stirring was stopped. The aging was continued for 1 hour. When the pressure in the autoclave dropped to a constant level, the material was cooled and discharged. The reaction product was neutralized with acetic acid, and the lower layer of opaque material was removed after standing for stratification to obtain 165 parts by weight of the polyether intermediate (ii), and the calculated yield was 93wt%. (The yield here is: the actual yield of the target product as a percentage of the theoretical yield calculated based on the complete reaction of the intermediate tetrapolyol, the same below)

[0112] The product is passed through1 H NMR characterization results are shown in Figure 2 As shown. The peaks in the figure belong to the following:

[0113] 1 H NMR (CDCl3, 400MHz): δ=0.880(-CH3), 1.259(CH3-(CH2) 11 -CH-), 2.430-2.675(-N-CH2-), 3.606-3.703(-O-CH2-CH2-O-).

[0114] By calculating the peak area ratio of the spectrum, the average value of the s value in the polyether intermediate (ii) was obtained to be 4.

[0115] (3) Weigh 10g of the polyether intermediate (ii) (6.6mmol) and dissolve it in 10g of dichloromethane. Slowly add 3.85g of chlorosulfonic acid (33mmol) at 0°C. After the addition is complete, gradually warm the temperature to room temperature. After reacting for 3 hours, slowly add 5mL of water to quench the excess unreacted chlorosulfonic acid. Subsequently, the solvent is removed by rotary evaporation, and the residue is dissolved in 50mL of ethanol. NaOH is slowly added to adjust the pH to 7-8. The precipitated solid is filtered out, and the filtrate is rotary evaporated to remove the solvent to obtain a crude product. The crude product is recrystallized in a mixed solvent of ethanol / ethyl acetate in a volume ratio of 1 / 5 to precipitate 8.14g of pure product with a yield of 65%. (The yield here is: the actual yield of the target product as a percentage of the theoretical yield calculated based on the complete reaction of the polyether intermediate, the same as in the following examples)

[0116] The product was characterized by infrared spectroscopy. Figure 3 As shown in the figure, the product is at 1221cm -1 The characteristic stretching vibration peak of the S=O bond contained in the sulfate ester group appears at , proving that the intermediate is successfully sulfonated to obtain the product surfactant, which is recorded as TES. The molecular weight of the surfactant is calculated to be 2021.10 g / mol.

[0117] Example 2

[0118] The anionic nonionic hexameric surfactant HES has the following preparation process:

[0119]

[0120] (1) 1.5 g (10 mmol) of tris(2-aminoethyl)amine was added to a solution of 19.1 g (90 mmol) of 1,2-epoxytetradecane in anhydrous ethanol (50 mL) and reacted at 50° C. for 24 h. After the reaction, the anhydrous ethanol solvent was removed by a rotary evaporator, and the crude product was dissolved in dichloromethane, and then purified by silica gel chromatography with dichloromethane / methanol and vacuum dried to obtain 13.9 g of the intermediate hexamer alcohol (i), with a calculated yield of 98 wt%.

[0121] The intermediate hexamer alcohol (i) was characterized by MALDI-TOF mass spectrometry. Figure 4 A peak of 1421.030 appeared in the spectrum, which was the molecular ion peak of the intermediate hexamer alcohol, proving that the target structure was obtained.

[0122] (2) 100 parts by weight of the intermediate hexamer alcohol (i) is added to a high-pressure reactor, and then 1 part by weight of KOH catalyst is added. The reactor body is sealed, and the air in the autoclave, the feed kettle and the feed pipe is displaced with dry nitrogen. The temperature is raised and stirred, and vacuum is evacuated with a vacuum pump at the same time. When the temperature rises to 100°C, the vacuum is stopped. 185 parts by weight of ethylene oxide is added to the feed kettle, pressurized to 0.4 MPa, mechanical stirring is turned on, and then the feed valve is opened to slowly feed the material. During the process, the reaction temperature is controlled at 160°C and the pressure is controlled at 0.4 MPa. After the addition is completed, the reaction is stopped for 8 hours and the stirring is stopped. The aging is continued for 1 hour. When the pressure in the kettle drops to a constant level, the material is cooled and discharged. The reaction product is neutralized with acetic acid, and the lower layer of opaque material is removed after standing and stratification, so as to obtain 190.4 parts by weight of the polyether intermediate (ii), and the calculated yield is 90wt%.

[0123] The polyether intermediate (ii) is 1 H NMR characterization results are shown in Figure 5 As shown. The peaks in the figure belong to the following:

[0124] 1 H NMR (CDCl3, 400MHz): δ=0.880(-CH3), 1.258-1.451(CH3-(CH2) 11 -CH-), 2.554(-N-CH2-, -N-CH2-CH-), 3.648-3.716(-O-CH2-CH2-O-).

[0125] By calculating the peak area ratio of the spectrum, it can be seen that the average s value in the polyether intermediate (ii) is 6.

[0126] (3) Weigh 10 g of the polyether intermediate (ii) (3.2 mmol) and dissolve it in 10 g of dichloromethane. Slowly add 2.9 g of chlorosulfonic acid (25 mmol) at 0°C. After the addition is complete, gradually warm the temperature to room temperature. After reacting for 6 hours, slowly add 5 mL of water to quench the excess unreacted chlorosulfonic acid. Subsequently, the solvent is removed by rotary evaporation, and the residue is dissolved in 70 mL of ethanol. NaOH is slowly added to adjust the pH to 7-8. The precipitated solid is removed by filtration, and the filtrate is rotary evaporated to remove the solvent to obtain a crude product. The crude product is recrystallized in a mixed solvent of ethanol / ethyl acetate in a volume ratio of 1 / 5 to precipitate 7.1 g of pure product with a yield of 60%.

[0127] Figure 3 The infrared spectrum of the product is given. In the figure, the product has a peak at 1221 cm -1 The characteristic stretching vibration peak of the S=O bond contained in the sulfate group appears at , proving that the intermediate is successfully sulfonated to obtain the product. The molecular weight of the surfactant is calculated to be 3616.01 g / mol.

[0128] Example 3

[0129] Anionic nonionic dimer surfactant DES:

[0130]

[0131] (1) 0.9 g (10 mmol) of N,N'-dimethylethylenediamine was added to a solution of 6.4 g (30 mmol) of 1,2-epoxytetradecane in anhydrous ethanol (50 mL) and reacted at 30°C for 24 h. After the reaction, the anhydrous ethanol solvent was removed by a rotary evaporator, the crude product was dissolved in dichloromethane, and then purified by silica gel chromatography with dichloromethane / methanol and vacuum dried to obtain 4.6 g of the intermediate dimer alcohol (i), with a yield of 90%.

[0132] The intermediate dimer alcohol (i) was characterized by MALDI-TOF mass spectrometry. Figure 6 A peak of 513.5391 appeared in the spectrum, which was the molecular ion peak of the intermediate dimer alcohol, proving that the target structure was obtained.

[0133] (2) 100 parts by weight of the intermediate dimer alcohol (i) was added to the autoclave, and then 0.25 parts by weight of KOH catalyst was added, the autoclave was sealed, and the air in the autoclave, the feed kettle and the feed pipe was displaced with dry nitrogen. The temperature was raised and stirred, and vacuum was evacuated with a vacuum pump at the same time. When the temperature reached 100°C, the vacuum was stopped. 86 parts by weight of ethylene oxide was added to the feed kettle, pressurized to 0.4 MPa, mechanical stirring was started, and then the feed valve was opened to slowly feed the material. During the process, the reaction temperature was controlled at 120°C and the pressure was controlled at 0.4 MPa. After the addition was completed, the reaction was stopped for 5 hours and the stirring was stopped. The aging was continued for 1 hour. When the pressure in the autoclave dropped to a constant level, the material was cooled and discharged. The reaction product was neutralized with acetic acid, and the lower layer of opaque material was removed after standing for stratification to obtain 138 parts by weight of polyether intermediate (ii), with a yield of 91wt%.

[0134] The polyether intermediate (ii) is 1 H NMR characterization results are shown in Figure 7 As shown. The peaks in the figure belong to the following:

[0135] 1 H NMR (CDCl3, 400MHz): δ=0.879(-CH3), 1.259(CH3-(CH2) 11 -CH-), 2.267-2.308(-N-CH2-, -N-CH3), 3.647(-O-CH2-CH2-O-).

[0136] By calculating the peak area ratio of the spectrum, it can be seen that the average s value of the polyether intermediate (ii) is 3.

[0137] (3) Weigh 10 g of the polyether intermediate (ii) (13.9 mmol) and dissolve it in 10 g of dichloromethane. Slowly add 3.4 g of chlorosulfonic acid (29 mmol) at 0°C. After the addition is complete, gradually warm the temperature to room temperature. After reacting for 2 hours, slowly add 5 mL of water to quench the excess unreacted chlorosulfonic acid. Subsequently, the solvent is removed by rotary evaporation, and the residue is dissolved in 40 mL of ethanol. NaOH is slowly added to adjust the pH to 7-8. The precipitated solid is removed by filtration, and the filtrate is rotary evaporated to remove the solvent to obtain a crude product. The crude product is recrystallized in a mixed solvent of ethanol / ethyl acetate in a volume ratio of 1 / 5 to precipitate 8.6 g of pure product with a yield of 68%.

[0138] Figure 3 The infrared spectrum of the product is given. In the figure, the product has a peak at 1221 cm -1 The characteristic stretching vibration peak of the S=O bond contained in the sulfate ester group appears at , proving that the intermediate is successfully sulfonated to obtain the product. The molecular weight of the surfactant is calculated to be 980.56 g / mol.

[0139] Example 4

[0140] The method of Example 1 is followed, except that the amount of ethylene oxide added in step (2) is 1080 parts by weight. By calculating the peak area ratio of the spectrum, the average value of the s value in the polyether intermediate is 32.

[0141] The obtained polyether intermediate was subjected to sulfonation reaction in the same manner, and the obtained product was recorded as TES-2. The molecular weight of the surfactant was calculated to be 6952.04 g / mol.

[0142] Comparative Example 1

[0143] A commercially available single-chain anionic nonionic surfactant, sodium lauryl polyoxyethylene ether sulfate (SLES), was used as a surfactant.

[0144] Test Example 1: Calcium and magnesium ion resistance

[0145] Determination of calcium / magnesium ion resistance: Weigh 1g of the surfactants in the above examples and comparative examples respectively, and dissolve them in 100mL of a sodium chloride aqueous solution with a mass concentration of 100000mg / L at room temperature. Then, add anhydrous calcium chloride to the surfactant aqueous solution in batches, adding 0.05g each time, and observe the state of the solution after sufficient stirring and dissolution. If no precipitation is precipitated, continue to add anhydrous calcium chloride, and repeat this process until precipitation is produced in the solution. Calculate the mass concentration of calcium ions in the solution at this time, and define this concentration as the calcium ion limit tolerance concentration C of the surfactant. Ca The magnesium ion limit tolerance concentration C of the surfactant can be measured by replacing the calcium chloride used in the above step with magnesium chloride. Mg .

[0146] Determine the C of the above examples and comparative examples Ca and C Mg The results are shown in Table 2.

[0147] Table 2

[0148] Surfactants <![CDATA[C Ca / (mg / L)]]> <![CDATA[C Mg / (mg / L)]]> TES 21500 13500 HES 20000 13000 DES 7000 4500 TES-2 19500 12500 SLES 1000 500

[0149] It can be seen from the results in Table 2 that the calcium and magnesium ion resistance of the anionic nonionic surfactant provided by the present invention is significantly improved compared with the single-chain SLES. The calcium and magnesium ion tolerance limit concentration of the anionic nonionic tetrasulfate surfactant TES is the highest, and its upper limits of tolerance to calcium and magnesium ions can be as high as 21500 mg / L and 13500 mg / L, respectively. The calcium and magnesium ion resistance of the same type of hexameric surfactant HES is relatively close to that of TES. In addition, from the comparison between TES and TES-2, it can be seen that when the s value is too large, the calcium and magnesium ion resistance of the surfactant decreases. This may be due to the folding of too many ethoxy groups on the surface of the molecular aggregate, which brings about greater steric hindrance, thereby weakening the calcium and magnesium resistance of the molecule. The calcium and magnesium ion resistance of the same type of dimeric surfactant DES decreases more, and its upper limits of tolerance to calcium and magnesium ions are reduced to 7000 mg / L and 4500 mg / L, respectively, which may be due to its low degree of oligomerization. But even so, its C Ca and C Mg The concentrations of the two surfactants are still 7 and 9 times that of SLES, respectively. This enables the novel anionic nonionic oligomeric surfactant synthesized by the present invention to be well adapted to the formation water of high calcium and magnesium oil reservoirs without precipitation.

[0150] Test Example 2: Interfacial Activity and Critical Aggregation Concentration

[0151] The oil-water interfacial tension of the anionic nonionic surfactants of the embodiments and comparative examples at different concentrations was measured using a TX-500C interfacial tension meter with a spinning drop method.

[0152] The test oil is crude oil from an oil field in Xinjiang (its viscosity at 50°C is 5577mPa·s measured by Haake VT550 rotational viscometer). The test water is formation mineralized water with a total mass concentration of calcium and magnesium ions of 7000mg / L and a mineralization of 100000mg / L. The test process controlled the test temperature to 50°C and the rotation speed to 5000rpm. During the test, as the surfactant concentration increased, the oil-water interfacial tension value continued to decrease. After a certain critical concentration, the interfacial tension value remained basically stable and a platform area appeared (if the concentration doubled again and the interfacial tension value change rate did not exceed 5%, it was considered stable). The concentration of the surfactant at this time was defined as the critical aggregation concentration (CAC), and the interfacial tension value of the platform area was defined as the interfacial tension of the surfactant. The results are shown in Table 3.

[0153] Table 3

[0154] Surfactants Interfacial tension / (mN / m) CAC / (mg / L) TES 0.07 500 HES 0.09 850 DES 0.27 920 TES-2 0.11 900 SLES 4.52 -

[0155] As shown in Table 3, the tetrameric and hexameric anionic nonionic surfactants prepared by the present invention can still reduce the oil-water interfacial tension of the target crude oil by 10 in high calcium and magnesium and high mineralization formation water.-2 mN / m range, maintaining good interfacial activity. In contrast, the interfacial activity of dimeric anionic nonionic surfactants is weakened, and the interfacial tension is 10 -1 mN / m range, it still has interfacial activity. Under the same conditions, SLES becomes a precipitate without interfacial activity, and its measured interfacial tension value is as low as 4.52mN / m. There is no inflection point in the interfacial tension curve as the concentration changes, so there is no CAC value under this condition. From the comparison between TES and TES-2, it is found that too large an s value is also not conducive to the aggregation of molecules and the close arrangement of molecules at the oil-water interface, and the reason is consistent with the analysis of the above test example 1.

[0156] Test Example 3: Viscosity reduction test of heavy oil

[0157] The test oil was taken from a certain oil field in Xinjiang, with a viscosity of 5577 mPa·s at 50°C, which is ordinary heavy oil. The test water was formation mineral water with a total mass concentration of calcium and magnesium ions of 7000 mg / L and a mineralization of 100000 mg / L.

[0158] The specific test steps for heavy oil viscosity reduction are as follows:

[0159] (a) Take 20 mL of heavy oil sample and place it in a distillation flask;

[0160] (b) The surfactants in the examples and comparative examples were respectively prepared with test water into 1000 mg / L aqueous solutions, and 10 mL of the prepared 1000 mg / L aqueous solutions were respectively added to the distillation flask containing the heavy oil sample;

[0161] (c) stirring the mixture at 50° C. for 1 min to obtain a crude oil emulsion, and then measuring the viscosity of the crude oil emulsion at 50° C. using a Haake VT550 rotational viscometer;

[0162] (d) The viscosity reduction rate of heavy oil is calculated using the following formula based on the measured viscosity data:

[0163] M=[(η1-η2) / η1]×100%;

[0164] In the above formula, η1 refers to the viscosity of crude oil (mPa·s); η2 refers to the viscosity of crude oil emulsion (mPa·s);

[0165] M is the viscosity reduction rate.

[0166] The viscosity reduction effects of the surfactants prepared in various embodiments are shown in Table 4.

[0167] Table 4

[0168]

[0169]

[0170] As can be seen from the results of Table 4, the anionic nonionic oligomeric surfactants provided by the present invention can emulsify the target heavy oil into an oil-in-water emulsion, achieve efficient viscosity reduction of the heavy oil, and the viscosity reduction rate of the heavy oil is higher than 97%. In contrast, the same type of single-chain surfactant SLES is precipitated in high calcium and magnesium ion mineralized water and does not have an emulsification viscosity reduction effect. In addition, the comparison of TES and TES-2 shows that for the target heavy oil, TES with a smaller s value has a closer hydrophilic-lipophilic balance. The s value of TES-2 is too large, resulting in its relatively weak viscosity reduction effect. However, the method provided by the present invention can prepare oligomeric surfactants with different s values, and the hydrophilic-lipophilic balance values ​​of these surfactants are different, which provides more feasible solutions for the viscosity reduction development of heavy oils of different properties.

[0171] Combining the results of Table 2, Table 3 and Table 4, it can be seen that the novel anionic nonionic oligomeric surfactant provided by the present invention has a strong ability to resist calcium and magnesium ions. At the same time, in high calcium and magnesium, high mineralization formation water, the anionic nonionic oligomeric surfactant can be enriched at the oil-water interface, reduce the oil-water interfacial tension and interfacial Gibbs free energy, show good interfacial activity, and promote phase transition to form a low-viscosity water-in-oil emulsion, and finally achieve a viscosity reduction rate of more than 97%. Therefore, the novel anionic nonionic oligomeric surfactant provided by the present invention has broad application potential in the field of cold production viscosity reduction and production increase in high calcium and magnesium, high mineralization oil fields.

[0172] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An anionic nonionic surfactant, characterized in that The surfactant includes a compound having a structure shown in formula (I), Wherein, each R2 is independently selected from H, C1-C4 alkyl, R5 and R6 are each independently substituted or unsubstituted C8-C 22 Alkenyl, C8-C 22 alkyl or heteroalkyl, M is an alkali metal; each R4 is independently selected from H, C1-C4 alkyl or and at least one R2 or R4 is R1 and R3 are each independently selected from substituted or unsubstituted C1-C 20 of alkylene; In the surfactant, the average value of s value is 1-100.

2. The surfactant according to claim 1, wherein At least two R2 Or, at least two R2 are And in each R2, at least one R4 is Preferably, M is Na or K.

3. The surfactant according to claim 1 or 2, wherein The surfactant comprises at least one of the compounds having the following structural formula, 4. The surfactant according to any one of claims 1 to 3, wherein R1 and R3 are each independently selected from substituted or unsubstituted C1-C 12 of alkylene; Preferably, R1 and R3 are selected from any one of the structures shown in formula (1) to formula (16); 5. The surfactant according to any one of claims 1 to 4, wherein R5 and R6 are each independently n-octyl, n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, (2-ethylhexyloxy)methyl, octenyl or C8-C 10 Alkoxymethyl; Preferably, R5 is n-octyl, n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, (2-ethylhexyloxy)methyl, octenyl or C8-C 10 Alkoxymethyl, R6 is hydrogen; And / or, in the surfactant, the average value of s value is 2-20.

6. The surfactant according to any one of claims 1 to 5, wherein The molecular weight of the surfactant is no more than 10000 g / mol, preferably 400-8000 g / mol.

7. A method for preparing an anionic nonionic surfactant, characterized in that: The following steps are involved: (1) subjecting an amine compound to a first ring-opening reaction with a 1,2-epoxy compound to obtain an intermediate oligomer alcohol; Wherein, the amine compound has a structure shown in formula (i), Wherein, each R2' is independently selected from H, C1-C4 alkyl or Each R4' is independently selected from H or C1-C4 alkyl; R1 and R3 are independently selected from substituted or unsubstituted C1-C 20 Alkylene, C2-C 20 Heteroalkylene and C6-C 20 At least one of the arylene groups; The structure of the 1,2-epoxide compound is represented by R5 and R6 are each independently substituted or unsubstituted C8-C 22 Alkenyl, C8-C 22 An alkyl or heteroalkyl group; (2) in the presence of a base, subjecting the intermediate oligomeric alcohol to a second ring-opening reaction with ethylene oxide to obtain a polyether intermediate; (3) contacting the polyether intermediate with a sulfonating agent to carry out a sulfonation reaction to obtain a mixture; (4) using an alkaline substance containing an element M to adjust the pH value of the mixture to be greater than or equal to 7, and then performing solid-liquid separation; M is an alkali metal.

8. The preparation method according to claim 7, wherein: In formula (i), R1 and R3 are selected from linear or branched C1-C 12 Alkylene, C2-C 10 At least one of a heteroalkylene group and a disubstituted phenyl group; wherein the heteroatom in the heteroalkylene group is selected from at least one of O, S and N; Preferably, the amine compound is selected from at least one of the compounds having structures represented by formula (17) to formula (43); 9. The preparation method according to claim 7 or 8, wherein: R5 and R6 are each independently n-octyl, n-decyl, n-dodecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, (2-ethylhexyloxy)methyl, octenyl or C8-C 10 Alkoxymethyl; Preferably, the 1,2-epoxy compound is selected from 1,2-epoxydecane, 1,2-epoxytetradecane, 1,2-epoxyhexadecane, 1,2-epoxyoctadecane, 1,2-epoxyeicosane, 2-ethylhexyl glycidyl ether, 1,2-epoxy-9-decene and C8-C 10 At least one of alkyl glycidyl ethers.

10. The preparation method according to any one of claims 7 to 9, wherein: In step (1), the molar ratio of the 1,2-epoxy compound to the amine compound is (1-10):1, preferably (1.1-2):1, wherein the molar amount of the amine compound is based on the molar amount of the NH bond in the molecule; Preferably, the conditions of the first ring-opening reaction include: temperature of 30-150°C, time of 4-72h; Preferably, the first ring-opening reaction is carried out in the presence of an organic solvent, and the organic solvent is preferably at least one of methanol, ethanol, isopropanol and dichloromethane.

11. The preparation method according to any one of claims 7 to 10, wherein: In step (2), the mass ratio of ethylene oxide to the intermediate oligomeric alcohol is (20-1000):100, preferably (50-500):100; Preferably, the base is selected from alkali metal hydroxides, preferably sodium hydroxide and / or potassium hydroxide; Preferably, the mass ratio of the base to the intermediate oligomeric alcohol is (0.1-2):100, preferably (0.25-1):

100.

12. The preparation method according to any one of claims 7 to 11, wherein: The conditions of the second ring-opening reaction include: reaction temperature of 80-180°C, reaction time of 4-10h, reaction pressure of 0.3-1MPa; Preferably, the second ring-opening reaction comprises: mixing the intermediate oligomeric alcohol with a base at a first constant temperature, and then adding ethylene oxide to react at a second constant temperature, wherein the first constant temperature does not exceed 100° C., preferably 80-100° C., and the second constant temperature is 100-180° C., preferably 120-160° C.; Preferably, the second ring-opening reaction is carried out under stirring conditions.

13. The preparation method according to any one of claims 7 to 12, wherein: The sulfonating agent is selected from at least one of sulfur trioxide pyridine complex, oleum, sulfur trioxide, concentrated sulfuric acid, chlorosulfonic acid, and aminosulfonic acid; Preferably, the ratio of the molar amount of the sulfonating agent to the molar amount of the polyether intermediate is (0.5-3):1, preferably (1-1.5):1, wherein the molar amount of the polyether intermediate is based on the molar amount of the hydroxyl groups contained; Preferably, the alkaline substance is an alkali metal hydroxide, preferably at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide, more preferably sodium hydroxide and / or potassium hydroxide.

14. Use of the anionic nonionic surfactant according to any one of claims 1 to 6 or the anionic nonionic surfactant prepared by the preparation method according to any one of claims 7 to 13 in heavy oil viscosity reduction recovery.

15. A method for reducing the viscosity of heavy oil, comprising: Mixing the viscosity reducer with the heavy oil; The viscosity reducing agent comprises the surfactant described in any one of claims 1 to 6 or the anionic nonionic surfactant prepared by the preparation method described in any one of claims 7 to 13; Preferably, the total mass concentration of calcium and magnesium ions in the formation water of the reservoir where the heavy oil is located is higher than 6000 mg / L, and the total mineralization is higher than 80000 mg / L.

Citation Information

Patent Citations

  • Double hydrophilic head-based anionic surfactant and preparation method thereof

    CN105368426A

  • Oligomeric anion sulfonate surfactants, and preparation method and application thereof

    CN107973730A

  • Thickened oil emulsifying viscosity reducer as well as preparation method and application thereof

    CN115806812A

  • High performing laundry detergent

    WO2020064497A1

Cited By

  • Amphiphilic nickel catalyst, preparation method thereof and application of amphiphilic nickel catalyst in viscosity reduction of thickened oil

    CN121202735A